Ethik von Banken und Finanzen - Stüttgen, Manfred (Religion - Wirtschaft - Politik, 2017)
New rules of engagement are emerging in the financial industry. In addition to financial returns, non-economic elements are becoming increasingly important: investors are demanding sustainable investments, banks are claiming to be caring and environmentally aware, and those working in the capital market are having to prove that they are not only concentrating on making a profit but also on avoiding risks to society.This transdisciplinary anthology collates the research findings, critical reflections and new ideas of leading Swiss, German, Austrian, Canadian and American experts from the fields of investment, bank management, financial ethics and moral theology.Born in 1969, Dr. Manfred Stüttgen works as an advisor to banks, asset managers and foundations. He runs the company YNVESTOR AG and also teaches at the University of Lucerne and at the Institute of Financial Services (Institut für Finanzdienstleistungen) in Zug.